Total Protein Requirements of Beef Cattle III: Match the Diet to the Cattle Requirements - Matt Hersom; Jeffrey N. Carter (EDIS)
AN188, a 4-page fact sheet by Matt Hersom and Jeffrey N. Carter, is the third of a three-part series on protein requirements of beef cattle. It applies the knowledge from the first two parts in a realistic example, by providing descriptions of one beef cow in three different productive states, and the nutrient profiles of the corresponding diet. Includes a table showing how changes in diet quantity and nutrient composition affect cow body composition. Published by the UF Department of Animal Sciences, August 2007.